Slow fashion or self-signaling? Sustainability in the fashion industry - Duarte, Madalena Maria Silva Ferreira Migueis (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence